Impact of labour quality on labour productivity and economic growth - Jajri, I.; Ismail, R. (2010)
The growth of the Malaysian economy has gone through several phases and strategies from input-driven to productivity-driven and knowledge-based-driven, which is in line with the world scenario. The knowledge-based-driven of economic growth is crucial as it will raise level of competitiveness of the country, especially in facing the world challenges. This paper attempts to observe to what extent the Malaysian economy has benefited from educational expansion. The production and productivity functions are estimated using the quality of labour together with the capital stock as independent variables. The effective labour and the level of education obtained by the employment are used as indicators to measure quality of labour. The data used for the analysis are gathered from various government agencies and world reports and the coverage is from 1981 to 2007. The study reveals that the capital stock and capital-labour ratio played a major role in contributing to the Malaysian economic growth and labour productivity respectively. The effective labour did play a positive role in determining economic growth but its contribution is less than the physical labour. This paper suggests that the education system must be geared towards producing workforce that can efficiently be used in the labour market.